SPE Annual Technical Conference and Exhibition 2011
DOI: 10.2118/145298-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Fracture Conductivity Correlations for a Specific Limestone Based on Surface Characterization

Abstract: Acid-fracture conductivity prediction is a key aspect in acid fracturing design and consequently in the oil and gas production forecast and economic evaluation. Acid-fracture conductivity correlations have been developed for some groups of calcareous rocks with a wide range of properties distribution. The experimental part of these studies has been based on samples from quarries and outcrops. This paper presents the development of conductivity correlations, which differs from previous studies by focusing on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The application of the Nierode and Kruk (1973) correlation to the Quissamã-ESP limestone showed mean deviation of 112.4%, SD of 92.4%, maximum deviation of 456.1%, maximum deviation in the range of closure stress of normal production of 127.0% (Rodrigues 2011). Thus, the developed correlation represents a significant improvement in conductivity prediction for the Quissamã-ESP.…”
Section: Conductivity Correlation Based On Surface Characterization Pmentioning
confidence: 80%
See 4 more Smart Citations
“…The application of the Nierode and Kruk (1973) correlation to the Quissamã-ESP limestone showed mean deviation of 112.4%, SD of 92.4%, maximum deviation of 456.1%, maximum deviation in the range of closure stress of normal production of 127.0% (Rodrigues 2011). Thus, the developed correlation represents a significant improvement in conductivity prediction for the Quissamã-ESP.…”
Section: Conductivity Correlation Based On Surface Characterization Pmentioning
confidence: 80%
“…The full results of the experimental study can be found in Rodrigues (2011). This item presents only the data directly related to the main topic of this paper.…”
Section: Experimental Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations